The Same Reverberation Time in Two Identical Rooms does not Necessarily Mean the Same Levels of Speech Clarity and Sound Levels when We Look at Impact of different Ceiling and Wall Absorbers. (November 2015) - Campbell, Colin; Nilsson, Erling; Svensson, Carsten
Abstract: For setting the acoustic conditions in a classroom for teaching and learning activities, it is common to only measure Reverberation Time (RT). To calculate the RT in rooms with ceiling absorption is common but this data can also be misleading. Indeed, we measured the similar RT values in two identical rooms with different acoustic treatment, even though the calculations predicted significant differences and interestingly the rooms are also be perceive quite differently in reality. Taking the human response to sound into account the measured RT data alone leaves us in the dark when seeking to explain the difference in human user perception. Measuring additional room acoustic parameters such as speech clarity and the difference in sound levels, identifies other important differences between the two unoccupied but furnished rooms with the same RT and points to why only one of the two rooms seems fit for purpose as a group activity room. We will discuss how to achieve room acoustic comfort in classrooms; short RT, low sound levels and high speech clarity. In addition to commonly accepted short RT values we will discuss recommended objective values for good Speech Clarity to support good speech communication activities in typical teaching and learning rooms in real life situations.